Formulation of Business Development Strategies to Achieve Competitive Advantage - Muhammad Yogi Alfian; Arif, Moh. Erfan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Indonesia is a country whose most of its population work as farmers. This shows that agriculture is one of the potential sectors, with one of its sub-sectors, i.e., horticulture, is flourishing. such increase has intensified the competition and required the business player, especially those conducting their business in Pare Central Market – one of the largest vegetable markets, to apply strategies suitable with their characteristics and environments. After four years of operation, this business has not reached stability in income. In fact, its revenue continues to decrease. The objective is to analyze the internal and external factors of the greengrocery. The primary data was harvested via interviews and observations, while the secondary data was acquired from books, journals, and websites. The analytical instruments are IFE Matrix, EFE Matrix, SWOT Matrix, IE Matrix, and QSPM. The results indicate that the appropriate strategy to be applied by Toko Sayur Lesmana is market penetration with the TAS score of 5.23.